KALIMAT TANYA DALAM BAHASA INGGRIS DAN BAHASA TAA (SUATU ANALISIS KONTRASTIF) - KASIM, RISTANTI M.; PAKASI, JENNY HILDA; MARENTEK, ANDRIYANI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACT             This study is an attempt to analyze, describe, and contrast English and Taa language which focuses on the interrogative sentences in relation to their forms and functions in both languages. The data of the English language were collected from books by Aarts (2001) Azar (1996, 2003), Downing and Locke (2006), and Lou (2006), whereas the data of Taa language were collected by interviewing and recording using a mobile phone recording, resulting in the collected audio materials as the primary data. The data were then analyzed and described. To find out the forms and functions of interrogative sentences, the writer used theory of interrogative sentences based on Aarts (2001), Azar (1996, 2003), Downing and Locke (2006), Lou (2006), and Parera (1988). After that, the data were contrasted by using Lado’s theory (1971). The results of this study show that these two languages have differences as well as similarities. There are eight similarities and fifteen differences between both languages.       Keywords: Interrogative Sentences, English, Taa Language, Contrastive Analysis.